(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
+++++ The study empirically examined the impact of job satisfaction on employees’ productivity. The specific objectives were; to investigate the impact of job safety and security on employees’ productivity and to determine the extent to which promotion affect employees’ productivity. This study employed survey research design. A combination of secondary and primary sources of data was adopted in this study. Primary source of data principally was extracted from the questionnaire. The data collected from the field survey was presented and analyzed in tables and simple percentage format. Also, the Chi-square statistical tool was used in testing the research hypothesis. The major findings of the study include: There was a significant impact of job satisfaction on productivity, Job safety and security had a significant impact of employees’ productivity and there was a significant impact of promotion on employees’ productivity in hospitality firms. The study recommended that management should set up effective strategies that will lead to goals and objectives of the organization. Management should improve on job safety and security so that it will enhance high level of productivity. Good working conditions should be implemented in order to improve workers’ performance.